Freestanding Ge/GeO2 Core-Shell Nanocrystals with Varying Sizes and Shell Thicknesses: Microstructure and Photoluminescence Studies. (14th September 2011) - Giri, P. K.; Dhara, Soumen
Abstract : Freestanding Ge/GeO2 core-shell nanocrystals (NCs) with varying sizes and shell thicknesses were synthesized by a ball milling method. The core-shell NCs consist of single crystalline Ge core and crystalline GeO2 shell. With increasing milling time, sizes of the NCs decrease while GeO2 shell layer thicknesses increase. After 30 hours of milling, size of the core-shell NCs goes down to 11 nm. Analysis of high-resolution transmission electron microscope images revealed the presence of strain in the NCs and lattice distortion/dislocations in the Ge core near the interface of Ge core and GeO2 shell. This induced a strong phonon localization effect as evident from Raman studies and leads to enhanced radiative recombination, resulting in intense photoluminescence. Strong photoluminescence peaks in the visible and UV region were observed from all the samples and are attributed to Ge/GeO2 interface defect states. Optical Raman scattering studies confirm the formation of strained Ge/GeO2 core-shell NCs with varying thicknesses.